Bioactive natural alkaloid 6−Methoxydihydrosanguinarine exerts anti−tumor effects in hepatocellular carcinoma cells via ferroptosis - Han, Linfen; Gao, Chengchang; Jin, Xiaorui; Li, Yingping; Chen, Liangjie; Li, Donglin; Deng, Qinqin; Bian, Xueli (Frontiers in Pharmacology, 2025)
IntroductionFerroptosis is a form of regulated cell death driven by the accumulation of iron–dependent lipid peroxides, and ferroptosis–mediated cancer therapy has gained considerable attention. Despite emerging evidence that ferroptosis induction effectively suppresses hepatocellular carcinoma (HCC) progression and enhances chemosensitivity, the development of resistance to ferroptosis‐targeting therapies remains a critical challenge. Natural active compounds have great potential in cancer treatment.MethodsThe impact of 6-ME on the cell viability of HCC cells was assessed using the Cell Counting Kit-8 (CCK‐8) assay and colony formation assay. Furthermore, cellular morphology of HCC cells was visualized under inverted fluorescence microscopy. Intracellular reactive oxygen species (ROS) and lipid peroxidation levels were quantified using fluorescence probes and determined by flow cytometry analysis. The expression of ferroptosis-related proteins and genes was determined via Western blot and quantitative real-time PCR analyses.ResultsHere, we demonstrate that 6–Methoxydihydrosanguinarine (6–ME), an alkaloid from Macleaya cordata, exerts anti–tumor functions in HCC cells via ferroptosis. Stimulation with 6–ME induces intracellular ROS production, cell growth inhibition, and cell death in HCC cells, and these effects can be weakened by the ROS scavenger GSH or NAC and ferroptosis inhibitors deferoxamine mesylate (DFO) or ferrostatin–1 (Fer–1). Mechanistically, 6–ME downregulates the expression of the key ferroptosis defense enzyme GPX4 at the transcriptional level, leading to excessive lipid peroxidation and ferroptosis in HCC cells. Importantly, low concentrations of 6–ME also enhanced the ferroptosis sensitivity induced by RSL3 and IKE in HCC cells.ConclusionThese findings reveal that the natural product 6–ME exerts anti–tumor functions in HCC cells via ferroptosis and underscore the potential of 6–ME administered alone or in combination with canonical ferroptosis inducers for the treatment of HCC patients.